Microneedle‐Based Local Delivery of CCL22 and IL‐2 Enriches Treg Homing to the Skin Allograft and Enables Temporal Monitoring of Immunotherapy Efficacy (Adv. Funct. Mater. 44/2021). (26th October 2021) - Puigmal, Núria; Dosta, Pere; Solhjou, Zhabiz; Yatim, Karim; Ramírez, Cynthia; Choi, John Y.; Alhaddad, Juliano B.; Cosme, Ana Paula; Azzi, Jamil; Artzi, Natalie
Abstract : Microneedle Arrays In article number 2100128, Jamil Azzi, Natalie Artzi, and co‐workers present a theranostic microneedle‐based platform for the simultaneous delivery of immune modulators and sampling of skin interstitial fluid to monitor the response to the therapy. Using a model of allogeneic skin transplant in mice, they show that the microneedle‐mediated delivery of the therapy can help regulate the immune system locally, without inducing systemic immune suppression, increasing the prospects of graft survival.